Ethical and Scientific Claims in Aesthetic Medicine: A Bibliometric Analysis of Scopus?Indexed Literature - Esthy Yuliana; Mahendro Prasetyo Kusumo (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Background: The rapid growth of aesthetic medicine has been accompanied by increasing use of clinical, scientific, ethical, and promotional claims, particularly in digitally mediated environments where communication shapes patient expectations and decision-making. However, the literature addressing these claims remains fragmented across clinical, ethical, and medicolegal domains.This study aims to map the intellectual structure, thematic interconnections, and temporal evolution of research on claims in aesthetic medicine.A bibliometric analysis was conducted using Scopus-indexed publications retrieved on May 1, 2026. The initial search yielded 935 documents, of which 95 met the final inclusion criteria after sequential filtering. The dataset covered publications from 2005 to 2025. Analysis was performed using VOSviewer through keyword co-occurrence mapping, supported by thesaurus-based normalization. Network, overlay, and density visualizations were applied to  The analysis identified four interconnected thematic groups: (1) medicolegal and ethical claims, (2) clinical outcomes and procedural evaluation, (3) procedural and surgical techniques, and (4) ethical–relational dimensions. Clinical outcome evaluation emerged as the central basis for claim substantiation, while ethical and medicolegal issues—such as informed consent and malpractice—were structurally embedded within clinical research rather than peripheral. Communication and marketing-related keywords functioned as bridging elements across clusters. Temporal analysis demonstrated a shift from procedural emphasis toward increasing focus on outcome evaluation, ethical accountability, and governance.Claims in aesthetic medicine develop within an interconnected ecosystem linking clinical evidence, communication practices, and legal accountability. The findings highlight the need for alignment between scientific evidence, ethical communication, and promotional practices to support patient safety, trust, and professional legitimacy.